Jurassic tetrapod tracks from Italy: a training ground for many generations of researchers - Petti, Fabio Massimo; Avanzini, Marco; Antonelli, Matteo; Bernardi, Massimo; Leonardi, Giuseppe; Manni, Riccardo; Mietto, Paolo; Pignatti, Johannes; Piubelli, Daniele; Sacco, Enrico; Wagensommer, Alexander (Journal of Mediterranean Earth Sciences, 2020)
This article reports the state of the art of research on the Jurassic tetrapod footprints from Italy. All the sites discovered so far are characterized by dinosaur footprints and located in the Southern Alps (Northeastern Italy, Veneto, Trentino Alto-Adige) with the exception of the Mattinata tracksite (Southern Italy, Gargano Promontory, Apulia). The tracksites from the Southern Alps belong to four distinct stratigraphic horizons of the Lower Jurassic Calcari Grigi Group whereas the Mattinata track-bearing blocks are doubtfully assigned to the Upper Jurassic Sannicandro Formation (Kimmeridgian-Tithonian). For each site information is provided on the geographical and geological setting, age, ichnotaxonomy and possible trackmakers. The history of the discoveries, the evolution of the ichnological knowledge and the study techniques adopted through time are also described.